Cognitive impairment among patients with multiple sclerosis: associations with employment and quality of life - Campbell, J; Rashid, W; Cercignani, M; Langdon, D (Postgraduate medical journal, 2017)
ObjectivesTo explore the relationship between cognitive impairment and conventional measures of disability in multiple sclerosis (MS), quality of life (QOL) and employment status using the brief international cognitive assessment for multiple sclerosis (BICAMS) in the routine outpatient clinic.Methods62 patients with MS were assessed on the BICAMS test battery for cognitive impairment. Data were obtained on employment status and a number of questionnaires completed including fatigue severity score, multiple sclerosis neuropsychological questionnaire, hospital anxiety and depression scale, the functional assessment of multiple sclerosis (FAMS) as well as on the EuroQOL five dimension questionnaire (EQ-5D). Other assessments include the patient activation measure and unidimensional self-efficacy scale for multiple sclerosis.ResultsCognitive assessment revealed 44 subjects (65%) had evidence of cognitive impairment on formal testing. In comparison with patients without evidence of cognitive impairment, cognitively impaired patients exhibited significantly higher rates of unemployment (p=0.009). The symbol digits modalities test was the most significant predictor of unemployment. Cognitive impairment was associated with lower QOL scores on the FAMS (p=0.001) and EQ-5D (p<0.001).ConclusionsBICAMS provides a sensitive and easy to administer screening test for cognitive impairment within the outpatient setting. Cognitive impairment is common in our cohort of patients with MS attending outpatients and appears to be associated with increased rates of unemployment and lower measures of QOL.